2015
DOI: 10.17219/acem/40472
|View full text |Cite
|
Sign up to set email alerts
|

The Pitfalls and Important Distances in Temporal Bone HRCT of the Subjects with High Jugular Bulbs – Preliminary Report

Abstract: Background. High jugular bulb (HJB) may be detected unilaterally or bilaterally in temporal bone high resolution computerized tomography (HRCT). Objectives. In this retrospective study, we investigated the pitfalls and important surgical distances in patients with unilateral and bilateral HJB via temporal bone HRCT. Material and Methods. In this preliminary report, the study group consisted of 20 adult patients (12 male, 8 female), or 40 ears, all of which underwent temporal bone HRCT. We divided them into gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…Because of its close relationship with the pneumatized petrous bone, this can be the cause for pulsatile tinnitus. 2 Identification of a high jugular bulb has great value when planning surgeries through the temporal bone and some authors have tried to correlate this with other anatomic findings 25 . The study by Friedmann et al 7 showed that jugular bulbs were not detected in patients younger than two years, became enlarged in adulthood, and remained stable in the elderly.…”
Section: Discussionmentioning
confidence: 99%
“…Because of its close relationship with the pneumatized petrous bone, this can be the cause for pulsatile tinnitus. 2 Identification of a high jugular bulb has great value when planning surgeries through the temporal bone and some authors have tried to correlate this with other anatomic findings 25 . The study by Friedmann et al 7 showed that jugular bulbs were not detected in patients younger than two years, became enlarged in adulthood, and remained stable in the elderly.…”
Section: Discussionmentioning
confidence: 99%
“…The upper limit of the jugular bulb is commonly found under the hypotympanum within the middle-ear cavity, 14,35 and an atypical presentation of the jugular bulb may be visualized as an upward extension of the bulb that invades into the hypotympanum. 35 Sasindran et al defines this extension of jugular bulb presenting in the middle-ear space with a thin or nonexistent bony septum as a high-riding jugular bulb (HRJB), which has been previously subclassified as "with dehiscence" or "without dehiscence."…”
mentioning
confidence: 99%
“…Anatomical variations of these vasculatures and their anomalies, such as protrusive SS, dehiscence SS, high or high riding JB, and JB dehiscence, are not rare in the TB 10 , 11 . For instance, high JB has been seen to occur in 6–20% of the population 11 .…”
Section: Introductionmentioning
confidence: 97%